Innovation in automotive telematics services: characteristics of the field and management principles. (1st January 2003) - Lenfle, Sylvain; Midler, Christophe
The growing role of innovation in the strategy of car manufacturers leads them to relentlessly look for new sources of differentiation. In this way, telematics, a suite of technologies centred on communications systems within cars, is expected to bolster the car industry by offering a new stream of revenues. This article focuses on the impact of this technology on design organisation. In the first part, we demonstrate that telematics is a radical innovation for automotive industry. Therefore, traditional design models, such as heavyweight project management, are unsuitable. Next, the paper studies the organisation adopted by a European car manufacturer in the light of recent research on the management of innovation.